2018
DOI: 10.1186/s13063-018-2509-7
|View full text |Cite
|
Sign up to set email alerts
|

The Strengthening Exercises in Shoulder Impingement trial (The SExSI-trial) investigating the effectiveness of a simple add-on shoulder strengthening exercise programme in patients with long-lasting subacromial impingement syndrome: Study protocol for a pragmatic, assessor blinded, parallel-group, randomised, controlled trial

Abstract: BackgroundSubacromial impingement syndrome (SIS) is a painful, and often long lasting, shoulder condition affecting patient function and quality of life. In a recent study, we observed major strength impairments in shoulder external rotation and abduction (~30%) in a population of patients with pronounced and long-lasting SIS. However, the current rehabilitation of such strength impairments may be inadequate, with novel rehabilitation programmes including exercise therapy only improving external rotation stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 56 publications
0
39
1
Order By: Relevance
“…Dichotomous secondary outcomes for treatment success included the Patient Acceptable Symptom State (PASS; acceptable/ unacceptable) and global impression of change (recovered or much improved, yes/no). Additional secondary outcomes will be reported in subsequent publications, as outlined in the trial protocol 10 and registration (ClinicalTrials.gov NCT02747251) (see the Appendix, available online).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dichotomous secondary outcomes for treatment success included the Patient Acceptable Symptom State (PASS; acceptable/ unacceptable) and global impression of change (recovered or much improved, yes/no). Additional secondary outcomes will be reported in subsequent publications, as outlined in the trial protocol 10 and registration (ClinicalTrials.gov NCT02747251) (see the Appendix, available online).…”
Section: Discussionmentioning
confidence: 99%
“…We applied constrained linear mixed models to compare the change in the IG with that in the CG, as described in the trial protocol. 10 Similar analyses were conducted for all continuous secondary outcomes. Dichotomous outcomes were compared between groups using chi-square tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,23,46,57 Second, we did not prescribe a home exercise program for either group in this study, as nonadherence has been reported in up to 70% of patients, 21 exercise diaries appear to be unreliable, 71 and many patients fail to appropriately dose or correctly perform their home exercise program. 11,22 Third, we did not use a placebo needling or control group. Although we recognize the use of a placebo needling group as an ideal situation, 45 our goal was to compare the novel intervention (TMEDN) to a more common physical therapy intervention (NTMEX) to more accurately determine the new treatment's effect size, 20,23,57 without the potential for an inflated between-group effect size.…”
Section: Discussionmentioning
confidence: 99%